Variation in students' experience of learning in an accelerated, residential, study abroad setting in comparison to their traditional HE experience - Jane MacKenzie (Association for Learning Development in Higher Education (ALDinHE), 2013)
This study explores the variation in students' learning experiences of studying accelerated, residential courses during a four week study abroad option at an international study centre in the UK compared with their experiences of learning at their home institution. In focussing on qualitative aspects of students' learning experiences in these settings, this study fills a gap in the accelerated course literature